Five-year forward view: lessons from emergency care at the extremes of age. (March 2018) - Minhas, JS; Minhas, D; Coats, T; Banerjee, J; Roland, D
Objective: The progressive rise in demand on NHS emergency care resources is partly attributable to increases in attendances of children and older people. A quality gap exists in the care provision for the old and the young. The Five Year Forward View suggested new models of care but that the "answer is not one-size-fits-all". This article discusses the urgent need for person-centred outcome measures to bridge the gap that exists between demand and provision. Design: This review is based on evidence gathered from literature searching across several platforms using a variety of search terms to account for the obvious heterogeneity, drawing on key 'think-tank' evidence. Settings: Qualitative and quantitative studies examining approaches to caring for individuals at the extremes of age. Participants: Individuals at the extremes of age (infants and older people). Main Outcome Measures: Understanding similarities and disparities in the care of individuals at the extremes of age in an emergency and non-emergency context. Results: There exists several similarities and disparities in the care of individuals at the extremes of age. The increasing burden of health disease on the economy must acknowledge the challenges that exist in managing patients in emergency settings at the extremes of age and build systems to acknowledge the traits these individuals exhibit. Conclusion: Commissioners of services must optimise the models of care delivery by appreciating the similarities and differences between care requirements in these two large groups seeking emergency care.